Pengaruh Modal Psikologis dan Totalitas Kerja terhadap Kesejahteraan Subjektif - Dian Maulida; Abdul Rahman Shaleh (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2017)
Abstract: This research examined the effect of psychological capital and the totality of work on the subjective well-being of employees. This study involved 169 employees of PT X, a state-owned mining company in Jakarta. Sampling conducted using non-probability sampling with accidental sampling technique. The instruments used consisted Flourishing Scale and Scale for Positive and Negative Scales (SPANE) modified by Diener et al. (2009), Psychological Capital Questionnaire 12 (PCQ-12) from Luthans et al. (2007), Utrecht work engagement Scale (UWES-9) from Balducci, Fraccaroli, and Schaufeli (2010). Data analysis technique was multiple regression analysis. Based on the results of major hypothesis testing, the first conclusion obtained from this study is that there is a significant influence of psychological capital and work engagement on the subjective well-being of employees of PT X. Then, the results showed that four variables regression coefficient value was significant, that is; (1) self-efficacy; (2) spirit; (3) dedication; and (4) absorption while three other variables are not significant. All of these variables have a positive effect on employee’s subjective well-being.Abstrak: Penelitian ini dimaksudkan untuk menguji pengaruh modal psikologis dan totalitas kerja terhadap kesejahteraan subjektif karyawan. Penelitian ini melibatkan 169 karyawan PT X, BUMN dalam bidang pertambangan di Jakarta. Pengambilan sampel yang dilakukan menggunakan non probability sampling dengan teknik accidental sampling. Alat ukur yang digunakan terdiri atas Flourishing Scale (FS) dan Scale of Positive and Negative Scale (SPANE) yang dimodifikasi dari Diener et al. (2009), Psychological Capital Questionnaire 12 (PCQ-12) dari Luthans et al. (2007), Utrecht work engagement Scale (UWES-9) dari Balducci, Fraccaroli, and Schaufeli (2010). Teknik analisis data adalah analisis regresi berganda.Hasil uji hipotesis menunjukkan bahwa terdapat pengaruh yang signifikan modal psikologis dan totalitas kerja terhadap kesejahteraan subjektif karyawanPT X. Kemudian, hasil uji hipotesis menunjukkan bahwa terdapat empat dimensi yang nilai koefisien regresinya signifikan, yaitu: (1) self-efficacy; (2) semangat; (3) dedikasi; (4) keterlarutan, sementara 3 variabel lain tidak signifikan.